Intensidade de pastejo e épocas de adubação nitrogenada em sistemas integrados de produção agropecuária - Aiolfi, Ricardo Beffart (2018)
Integrated crop-livestock systems are essential for seeking intensification of land use and sustainability of food production. The aim of this trail was to identify the effects of the interaction between different grazing intensities and times of nitrogen fertilization in an integrated crop-livestock system, comprehending an annual pasture followed by bean crop. The experiment was carried out from May 2016 to March 2017, in a private farm in the municipality of Abelardo Luz / SC. Randomized blocks with three replications, in a 2x2 factorial scheme experimental design was used. The first factor corresponded to the sward canopy height, characterized by two sward canopy heights (25 cm, high height) and low height (10 cm). The second factor was the time of nitrogen fertilization, applied either on pasture (NP) in the fall, or on the crop (NG), in the spring, at the dose of 200 Kg N-urea ha-1. Annual ryegrass cv. Winter star under continuous stocking was used during cool-season. The animals were Nelore and Charolais crossbred, weighting 252.6 ± 31.8 Kg and about 12 months aged. The nitrogen use during pasture phase promotes higher forage production than N-crop fertilization increasing carrying capacity and animal production. Low height with N fertilization promotes the highest animal productivity. Higher sward canopy height generates bigger stubble amount on the soil than low height pasture management. However, when a pasture is managed in higher height, there is greater heterogeneity in the stubble distribution on the soil. Regardless of pasture height management and nitrogen fertilization time, there is no deleterious effect on the physical traits of the soil. Soil chemical components are not significantly altered throughout the agricultural year. Bean yield is not affected by the height of pasture management neither the times of nitrogen fertilization.